Hydration in Hot Working Environments - Jeanine Beatty; Gail P. A. Kauwell (EDIS)
Are you at risk for heat-related illnesses? Summertime isn’t the only time you should be concerned about drinking enough water to stay hydrated. Workers in construction, landscaping, laundry, factory, farm, or restaurant settings, among others, often are faced with hot working environments year-round. These conditions can increase the risk for developing heat-related illnesses, so staying well hydrated is very important. This 3-page fact sheet was written by Jeanine Beatty and Gail P. A. Kauwell, and published by the UF Department of Family, Youth and Community Sciences, March 2012.